2021
DOI: 10.1016/j.biopha.2021.112221
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon and its possible impact on COVID-19: The viewpoint of traditional and conventional medicine

Abstract: The COVID-19 global epidemic caused by coronavirus has affected the health and other aspects of life for more than one year. Despite the current pharmacotherapies, there is still no specific treatment, and studies are in progress to find a proper therapy with high efficacy and low side effects. In this way, Traditional Persian Medicine (TPM), due to its holistic view, can provide recommendations for the prevention and treatment of new diseases such as COVID-19. The muco-obstruction of the airway, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…Glycyrrhiza glabra has an inhibition effect on SARS viral replication and modulates membrane fluidity (Vellingiri et al 2020). Cinnamomum verum has also been demonstrated to have an effect on COVID-19 (Yakhchali et al 2021). Our study showed that G. glabra and C. verum had been used as an infusion of the roots during COVID-19 infection.…”
Section: Status Of Medicinal Plants Used During Covid-19 and Its Impa...mentioning
confidence: 63%
“…Glycyrrhiza glabra has an inhibition effect on SARS viral replication and modulates membrane fluidity (Vellingiri et al 2020). Cinnamomum verum has also been demonstrated to have an effect on COVID-19 (Yakhchali et al 2021). Our study showed that G. glabra and C. verum had been used as an infusion of the roots during COVID-19 infection.…”
Section: Status Of Medicinal Plants Used During Covid-19 and Its Impa...mentioning
confidence: 63%
“…There is also pharmacological evidence for its anti-depressant effects. [25] Green tea-epigallocatechin gallate (EGCG) and black teatheaflavin plants contain copper (Cu), iron (Fe), manganese (Mn), selenium (Se), and zinc (Zn) from the soil. It is recommended for the prophylaxis and treatment of COVID-19 due to the antiviral, antibacterial, immunomodulatory, antioxidant, and anti-inflammatory effects of the polyphenols it contains.…”
Section: Discussionmentioning
confidence: 99%
“…However, the aqueous extract demonstrated no marked antiviral function, which implies that the antiviral potential of this herb is mainly contributed to its lipophilic compounds including carotenoids [29] . Saffron and cinnamon have also been well studied for their anti-COVID-19 potential 30 , 31 , 32 . Damask Rose another component of the TPM also used in this study has been evidenced to help the body to excrete the harmful watery phlegm humor highly susceptible to infection and therefore is a tonic of the lungs [10] .…”
Section: Discussionmentioning
confidence: 99%